Medieval jewelry and burial assemblages in Croatia : a study of graves and grave goods, ca. 800 to ca. 1450 - Sokol, Vladimir, 1948- (Leiden : Brill, 2016)
The Croatian medieval archaeological heritage from the 8th to the 15th century consists mostly of jewelry (earrings) findings from cemeteries. This book uses vertical and horizontal stratigraphy, on the basis of around 20,000 burial assemblages from 16 cemeteries (out of several hundred so far excavated in Croatia), to establish relative and absolute chronology of jewelry and burial architecture divided into three horizons and four phases in comparison with materials from neighboring regions of Europe.
Part 1, Graves and material culture -- 1, A History of Research -- 2, Cemeteries and Material Culture -- 3, Cemetery Stratigraphy and the Classification of Material Culture -- 4, Cemetery Horizons and Material Culture Phases -- 5, The Development of Material Culture: Earrings and Their Evolution -- 6, Grave Architecture -- Interpretation and general remarks -- 1, Croat burial rites and belief system -- 2, Stone cists : late antique or early medieval? -- 3, Burial customs -- 4, Burial horizons and churches -- 5, Cemeteries between the mountains and the River Sava -- Part 2, Earrings -- 1, Earrings as Grave Goods -- 2, Medieval Earrings in Croatia
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 9.-15. století; archeologické nálezy -- Chorvatsko; hroby -- Chorvatsko -- 9.-15. století; sepulkrální architektura -- Chorvatsko -- 9.-15. století; pohřební výbava -- Chorvatsko -- 9.-15. století; pohřební zvyky -- Chorvatsko -- 9.-15. století; hmotná kultura -- Chorvatsko -- 9.-15. století; náušnice -- Chorvatsko -- 9.-15. století; antiquities -- Croatia; graves -- Croatia -- 9th-15th centuries; sepulchral architecture -- Croatia -- 9th-15th centuries; funeral equipment -- Croatia -- 9th-15th centuries; funeralrites and ceremonies -- Croatia -- 9th-15th centuries; material culture -- Croatia -- 9th-15th centuries; earrings -- Croatia -- 9th-15th centuries; e-knihy online; monografie; obrazové publikace; e-books online; monographs; pictorial works